Comparative Evaluation of Sedative Effects of Oral Midazolam and Oral Ketamine in Combination with Inhalation Sedation for Pediatric Behavior Control during Dental Treatment - N Kaviani; A Eshghi; P Tabibian (Isfahan University of Medical Sciences, 2007)
Introduction: Oral route for conscious sedation is very easy to administer drugs and has good acceptance. Oral Midazolam and Ketamine provide the effective sedation. Also conscious sedation with combination techniques increases efficacy. N2O/O2 can be combined with other routes for conscious sedation. In this study the effectiveness of oral midazola-N2O and oral ketamine-N2O in behavioral management of children uncooperative during dental treatment was evaluated.Methods and Materials: In this study we randomly divided 60 healthy, uncooperative children of 3-7 years old in two groups. One group was administered Midazolam 0/5 mg/kg and another was administered Ketamine 6 mg/kg. After 15 minute N2O/O2 with 50%: 50% administrated. Scores of crying, consciousness, movement and general behavior are evaluated during dental procedure base on Houpt rating scale. Data were analyses with SPSS software.Results: In both groups efficacy of sedation was more than 90% and there were not statistically significant difference between two groups. In Midazolam group, consciousness during dental procedure was higher and recovery time was shorter.Conclusion: Results indicated that positive and good effect of oral Midazolam or Ketamine with nitrous oxide for sedation and control of movement in children during dental treatment. Because the easy of usage and low side effects we can use form this methods for children behavior control during dental procedures.Key words: Pediatric dentistry, Conscious sedation, Midazolam, Ketamine, N2O